Modifikasi Perilaku Terhadap Anak - Aziz Nuri Satriawan Aziz (LP2M Institut Agama Islam (IAI) Muhammadiyah Sinjai, 2020)
AbstractBehavior modification as behavior therapy, this technique is often used by educators and parents because its success is easily observed and easily appilied to other bwhaviors, is a soluble use of conditioning techniques in humans to produce changes in the frequency of certain behaviors, namely changing non-adaptive behavior, by leaving it, and adaptive behavior confirmed, behavior change is carried out with a carefully crafted experimental desaign, this behavior modification makes it possible to be realized to the actors to be changed ie change the maladaptive behavior towards adaptive behavior. This qualitative research was conducted on children in Kenteng sub-village, Sumberejo village, Sine Ngawi sub-district. Research subjects are parents, neighbors and children who have maladaprive behavior. At the end of the study showed that self-management techniques and social skills training is able to change the behavior of children both to anticipate so as not to behave negatively and eliminate negative behaviors and foster positive behavior.Keywords : behavior modification, self-management, social skills